An Insight into the Baltic Experimental Archaeology Summer School 2017 - Artūrs Tomsons (EXARC, 2018)
The Baltic Experimental Archaeology Summer School (BEASS) took place from July 17th to 23rd 2017 in Lucavsala, Riga, Latvia. For the first time it was organised outside Āraiši Archaeological museum park, because of the change of its status from a branch of the National History Museum back to the department of Amata local municipality near Cēsis.